Social and Educational Transformation Based on Amali Interpretation of QS. An-Nahl Verse 125 at the Madrasah Sabtu Ceria - Iflahul Kamal; Kharis Nugroho; Yeti Dahliana (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the implementation of the practical interpretation of QS. An-Nahl verse 125 in the Madrasah Sabtu Ceria program as a model of community-based non-formal Islamic education and its impact on social transformation in Kampung Gondang. The main focus of the study is on how the values of hikmah, mau'izhah hasanah, and mujadalah are implemented in the children's learning process and how this learning influences the religious behavior of children, families, and the wider community. This study uses a qualitative approach with a case study type. Data were collected through in-depth interviews, participatory observation, and documentation of program managers, community leaders, student mentors, parents, and students. Data analysis was carried out descriptively-analytically through the stages of data reduction, data presentation, and drawing conclusions, with validity strengthened through triangulation of sources and methods. The results of the study indicate that the application of the practical interpretation of QS. An-Nahl verse 125 in Madrasah Sabtu Ceria is able to improve children's religiosity and morals, which are reflected in the habit of worship, polite behavior, and social awareness. Furthermore, children act as triggers for change in the family by encouraging parental involvement in religious activities. This impact extends to the community level through increased socio-religious participation, mutual cooperation, and collective solidarity. This study concludes that Islamic education based on practical interpretation in community-based semi-TPA institutions is effective as a strategy for cultural da'wah and social transformation at the grassroots level.